ANALISIS KETERAMPILAN MENULIS KARANGAN NARASI PADA SISWA KELAS V SD INPRES MALLENGKERI BERTINGKAT MAKASSAR - Andi Alfiah Haerina; Andi Sukri Syamsuri; Syaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Writing is an important basic skill for students in the learning process. Many fifth-grade students of SD Inpres Mallengkeri Bertingkat Makassar experience difficulties in developing ideas and expressing them in a coherent and coherent sequence of written events. In addition, the narrative essays produced by students tend to be short and lack detail so that the story becomes less interesting. The purpose of this study was to analyze the narrative essay writing skills of fifth-grade students. The method used in this study was descriptive qualitative, with 29 students as research subjects. Data collection techniques used were observation, interviews, and documentation. Data validity was obtained from triangulation of techniques and sources, while data analysis was obtained using the interactive model of Miles and Huberman. The results of the study indicate that students' narrative essay writing skills are still in the sufficient and insufficient category and need to be improved through writing habits, strengthening reading literacy, and the application of more varied and contextual learning methods.